Pengaruh Sentrifugasi Spesimen Darah Anemia Terhadap Derajat Aglutinasi Pemeriksaan Golongan Darah Metode Slide - Handayani, Sri Puji; Sukeksi, Andri; Afriansyah, Muhammad Ardi (Department of Health Analyst, Politeknik Kesehatan, Kementerian Kesehatan Tanjungkarang, 2022)
Anemic patients often have low hemoglobin and red blood cell level, which on the slide method and ABO system blood type test is used to obtain low degree of agglutination. Addition of treatment of a centrifugation was used to obtain a stronger degree of agglutination. The purpose of this research was to determine the difference degree of agglutination between centrifuged and uncentrifuged blood specimens in anemic patients. Quasi experimental research with non-equivalent control group design was conducted in March 2022 at the Hematology Laboratory, Universitas Muhammadiyah Semarang. The research sample were 16 specimens of anemic patients for slide method and ABO system blood type test. All samples were checked for blood type testbefore being centrifuged, then re-checked after the centrifugation there only concentrated red blood cell deposit were taken with only a small amount of plasma. The data from the test were analyzed using the Kruskal Wallis method. Comparison anti-A, anti-B, and anti-AB between centrifuged and uncentrifuged blood specimens there was a significant difference (p value < 0,005 means p = 0,002). The result showed that there were effect by centrifugation for the degree of agglutination improved better in centrifuged if compared with uncentrifugedanemicpatients blood specimens on blood type test slide method.Â